Molecular Targeted Agent and Immune Checkpoint Inhibitor Co-Loaded Thermosensitive Hydrogel for Synergistic Therapy of Rectal Cancer - Zhang, Huaiyu; Zhang, Jiayu; Liu, Yilun; Jiang, Yang; Li, Zhongmin (Frontiers in Pharmacology, 2021)
Molecular targeted therapy has been proved effective in treatment of rectal cancer. Up-regulated expression of programmed death ligand-1 (PD-L1) was observed after the management of molecular targeted therapy, which made the therapeutic effect discounted. Tumours with higher PD-L1 expression were more sensitive and responsive to treatment of PD-L1 inhibitor. Therefore, the combination of molecular targeted therapy and immune checkpoint blockade makes sense. In this study, the copolymers of poly (ethylene glycol)-block-poly(L-leucine) (PEG-PLLeu) were synthesised as a thermosensitive hydrogel composite for consecutive release of regorafenib (REG) and BMS202. The mechanical properties of PEG-PLLeu were investigated, confirming that PEG-PLLeu (5 wt.%) was suitable for in situ injection as drug-delivery composite at low temperature and stable after sol-gel transition at body temperature. Importantly, the double drug loaded hydrogel showed superior antitumour activity over single drugs in an orthotopic rectal cancer model (CT26-Luc). Further analysis of the tumour tissues suggested that REG upregulated the expression of PD-L1 in tumour tissues. In addition, the immunosuppressive tumour microenvironment of CT26-Luc tumour was distinctly relieved under the effect of BMS202, as characterised by increased infiltration of CD8+ T cells in tumours and enhanced secretion of antitumour cytokines (IFN-γ and TNF-α). Moreover, the drug-loaded composite showed no obvious toxicity in histological analysis. Taken together, the administration of REG and BMS202 in the PEG-PLLeu composite could induce a synergistic effect in in situ treatment of rectal cancer without obvious toxicity, and thus represented a potential strategy for enhanced in situ therapeutic modality.